Comparison of the in vitro effects of saline, hypertonic hydroxyethyl starch, hypertonic saline, and two forms of hydroxyethyl starch on whole blood coagulation and platelet function in dogs. (2nd June 2015) - Wurlod, Virginie A.; Howard, Judith; Francey, Thierry; Schweighauser, Ariane; Adamik, Katja N.
Abstract Objective To compare the in vitro effects of hypertonic solutions and colloids to saline on coagulation in dogs. Design In vitro experimental study. Setting Veterinary teaching hospital. Animals Twenty‐one adult dogs. Interventions Blood samples were diluted with saline, 7.2% hypertonic saline solution with 6% hydroxyethylstarch with an average molecular weight of 200 kDa and a molar substitution of 0.4 (HH), 7.2% hypertonic saline (HTS), hydroxyethyl starch (HES) 130/0.4 or hydroxyethyl starch 600/0.75 at ratios of 1:22 and 1:9, and with saline and HES at a ratio of 1:3. Measurements and Main Results Whole blood coagulation was analyzed using rotational thromboelastometry (extrinsic thromboelastometry‐cloting time (ExTEM‐CT), maximal clot firmness (MCF) and clot formation time (CFT) and fibrinogen function TEM‐CT (FibTEM‐CT) and MCF) and platelet function was analyzed using a platelet function analyzer (closure time, CTPFA). All parameters measured were impaired by saline dilution. The CTPFA was prolonged by 7.2% hypertonic saline solution with 6% hydroxyethylstarch with an average molecular weight of 200 kDa and a molar substitution of 0.4 (HH) and HTS but not by HES solutions. At clinical dilutions equivalent to those generally administered for shock (saline 1:3, HES 1:9, and hypertonic solutions 1:22), CTPFA was more prolonged by HH and HTS than other solutions but more by saline than HES. No difference was found between the HES solutions or the hypertonic solutions. ExTEM‐CFT and MCF were impaired by HH and HTS but only mildly by HES solutions. At clinically relevant dilutions, no difference was found in ExTEM‐CFT between HTS and saline or in ExTEM‐MCF between HH and saline. No consistent difference was found between the 2 HES solutions but HH impaired ExTEM‐CFT and MCF more than HTS. At high dilutions, FibTEM‐CT and ‐MCF and ExTEM‐CT were impaired by HES. Conclusions Hypertonic solutions affect platelet function and whole blood coagulation to a greater extent than saline and HES. At clinically relevant dilutions, only CTPFA was markedly more affected by hypertonic solutions than by saline. At high dilutions, HES significantly affects coagulation but to no greater extent than saline at clinically relevant dilutions.